Active inclusion of immigrants in Poland - Maciej Duszczyk; Marek Góra (Institute for the Study of Labor (IZA), 2012)
Poland has traditionally been treated as an emigration country. Since recently Poland has been changing into an emigration-immigration country. The latter, namely immigration, was boosted by the European Union membership and by stable and strong growth of the country. In the last years, immigrants have started to play an important role in the Polish labour market, which creates an additional challenge for the institutional structure. At the same time the institutional framework for receiving immigrants, especially integration policy, has not been fully developed yet. It is addressed only to refugees and is provided mostly by NGOs who run various integration programmes (most often focused on providing language courses). Public expenditure on integration policies has recently increased. However, data on immigrants, integration in immigration policy and also its analysis are still scarce. In this paper we try to present and discuss the available information on immigration to Poland and instruments of integration policy in the context of the existing institutional framework. We propose also recommendations for the pre-integration and integration policy in Poland. The goal of the paper is modest since it is hardly possible to apply more sophisticated methods given the limited availability of information.
urn:nbn:de:101:1-201207125608
Keywords: J61; J68; Y80; 330; immigrants; integration policy; active inclusion; Einwanderung; Migranten; Soziale Integration; Migrationspolitik; Polen